Implantoprosthetic treatment options for an extremely narrow neutral zone in the anterior mandible* - Piotrowski, Paweł; Szyczewski, Tomasz; Mehr, Katarzyna (Journal of Stomatology, 2016)
Introduction. Prosthetic rehabilitation of the edentulous mandible with severe atrophy of the prosthetic field is still a current clinical problem. Obtaining denture retention through the use of intra-osseous implants is not always sufficient to achieve therapeutic success. The main problem in this particular clinical situation is a very narrow neutral space in the anterior mandible, which eliminates the use of the implantsupported overdenture. Aim of study. To present an alternative method of prosthetic rehabilitation of the edentulous mandible with an extremely narrow neutral zone. Clinical case. A 60-year-old patient with an edentulous mandible was implanted with three Sky Bredent implants in the anterior mandible (positions 31, 33, 43). Due to insufficient width of the neutral zone a PFM bridge supported on three implants in the anterior segment, and a framework denture with precise elements in the lateral segment were applied. Results and discussion. The applied method allows introduction of both fixed and removable dentures in a narrow neutral zone, while not interfering with speech articulation and improving the aesthetics of the lower part of the patient’s face